The Effect of Microstructures and Hardness Characteristics of Recycling Aluminium Chip AA6061/Al Powder On Various Sintering Temperatures - Ab Kadir, Muhammad Irfan; Mustapa, Mohammad Sukri; Rosli, Nurul Liyana; Yahya, Mohd Shahir; Mohamad, Mahmod Abd Hakim; Abd Rahim, Abd Khalil (International Journal of Integrated Engineering, 2018)
Aluminium is a metal that has been widely used for commercial applications in the transportation, construction and aerospace industries. Previous studies on recycling aluminium have shown that a lot of energy was used to recycle the aluminium by using conventional method. Therefore, this study was carried out to discover the effect of sintering temperature on physical and mechanical properties of the recycled aluminium chip (AA6061) and aluminium powder with the particle size of 25µm by using a direct conversion method which is the powder metallurgy has been used. The samples were fabricated by using hydraulic press machine at 9 tonnes for 20 minutes. Since this study was focused on the sintering temperature, the samples were sintered at four different temperatures which were 520°C, 552°C, 585°C and 617°C. This study involved two types of tests which were the physical and mechanical test. The physical test involved microstructure observation, density test, porosity test, whereas, the mechanical test involved hardness test. Based on the results obtained, it can be concluded that the sintered temperature at 552°C was the best result of sintered sample to obtained better physical and mechanical for the recycled aluminium chip (AA6061).